Chemical, Physical, and Sensory Properties of Bread with Popped Amaranth Flour - Chaquilla Quilca, Guadalupe (2026)
This study investigated the effect of substitution of wheat flour with popped amaranth flour in bread formulation on the chemical, physical, and sensory characteristics of breads. The raw and popped amaranth grain flours of four Peruvian varieties: Oscar Blanco, Centenario, Taray, and Imperial, were characterised for chemical composition and pasting properties using Rapid Visco-Analyzer (RVA). Both types of amaranth flour had a high nutritional value, but the peak and final viscosity of popped amaranth flour were closer to the wheat flour. Breads were formulated with the popped amaranth flour, at four substitution levels of 0, 10, 20, and 30%. A significant increase in contents of protein (around 12%) and raw fiber (more than 100%), and a decrease in carbohydrate content (around 6%) in breads at the highest substitution level compared to wheat bread were observed. At this substitution level, the RVA profile parameters, specific volume, pore area, and colour coordinates (L*, a*, and b*) differed significantly. In the sensory analysis using Flash profile technique, consumers identified that the Taray and Imperial bread varieties at 10 and 20% substitution level were similar to the wheat bread. Adding popped amaranth flour to bread improved the nutritional value, ensuring good physical and sensory properties. Popped amaranth flour can, thus, be an alternative to wheat flour in the development of healthy bakery products.